2014
DOI: 10.1111/1469-0691.12476
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex molecular testing for management of infectious gastroenteritis in a hospital setting: a comparative diagnostic and clinical utility study

Abstract: Laboratory diagnosis and clinical management of inpatients with diarrhoea is complex and time consuming. Tests are often requested sequentially and undertaken in different laboratories. This causes prolonged unnecessary presumptive isolation of patients, because most cases are non-infectious. A molecular multiplex test (Luminex(®) Gastrointestinal Pathogen Panel (GPP)) was compared with conventional testing over 8 months to determine diagnostic accuracy, turnaround times, laboratory costs, use of isolation fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 30 publications
4
77
0
1
Order By: Relevance
“…Ten studies [20][21][22][23][24][25][26][27]29,30 reported results of association between the comparator and the GPP test in sufficient detail by pathogen to allow the construction of 2 × 2 tables by pathogen. These studies are further characterised in Table 7 and contributed data to the meta-analysis in Pathogen-level positive and negative agreement.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies [20][21][22][23][24][25][26][27]29,30 reported results of association between the comparator and the GPP test in sufficient detail by pathogen to allow the construction of 2 × 2 tables by pathogen. These studies are further characterised in Table 7 and contributed data to the meta-analysis in Pathogen-level positive and negative agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Studies retrospectively included samples with confirmed gastroenteritis and negative controls 30 or prospectively included samples from patients with suspected gastroenteritis. [20][21][22][23][24][25][26][27]29 Comparator and GPP tests were both undertaken at the study site(s) in seven studies, [22][23][24][25][26][27]29 whereas one study sent the samples to reference laboratories for conventional testing, 30 one study sent the samples to Luminex for GPP testing 21 and one study sent the samples to BioFire for comparator testing. 20 Verification was undertaken on all discrepant samples by four studies, 20 29 The remaining three studies, 24,26,27 which did not undertake verification, assumed either that the comparator methods are the reference standard to calculate sensitivity and specificity 24,26 or assumed that the GPP assay is correct and did not calculate sensitivity and specificity because of the lack of a resolving assay.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations